Intensified phosphorus removal from synthetic wastewater by lab-scale horizontal sub-surface flow constructed wetlands using a mixture of coal slag and calcined ferralsols as substrate - Lê, Thị Vân (2020)
Chapter 1. Literature review: This Chapter provided overall information about environmental problems related to P pollution, the discharge standsards for P containing wastwater, numerous technologies for P decontamination from wastewater. In addition, the composition of swine wastwater after anaerobic treatment was investigated. Especially, this chapter focuses on the CWs, highlighting the roles of filter media and wetland plants. Chapter 2. Materials and methods: This Chapter introduced materials, methods and equipments used for this research. Also, the experimental set-up was described in details. Chapter 3. Result and discussion: This Chapter referred the results on calcination of Ferralsols for strengthenning its P removal ability, characterization of raw and calcined materials, adsorption behaviors, and treatment perfomance of the HSSF-CWs using the selected filter materials and plants, and side-effects of using materials in HSSF-CWs. Chapter 4. Conclusions and recommendations: This Chapter provided the key findings obtained from this results as well as suggestions for future research.